PENDAMPINGAN PENGENALAN TEKNOLOGI REALITAS VIRTUAL DALAM ADMINISTRASI SEKOLAH UNTUK MENINGKATKAN EFEKTIVITAS MANAJERIAL - Sundari, Sri; Etiyasningsih, Etiyasningsih (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This initiative aims to enhance the effectiveness of school administration at YIMI Educational Foundation in Gresik through the implementation of Virtual Reality (VR) technology. Technological advancements provide an opportunity to streamline administrative processes that were previously carried out manually, often resulting in inefficiencies. Therefore, this project introduces VR as a tool to improve efficiency and accuracy in administrative tasks. The methodology involves direct training and mentoring for administrative staff, introducing the use of VR devices for managing student data, scheduling, and budgeting. Staff members are given the opportunity to practice and are guided in integrating VR into their daily tasks. The results of this initiative indicate a significant improvement in the staff's proficiency in using VR, with a reduction in the time required to complete various administrative tasks. 88% of participants reported that VR increased their work efficiency. Although some technical challenges and initial resistance were encountered, solutions such as technical support and additional training successfully addressed these obstacles. Overall, the implementation of VR technology has proven to have a positive impact on enhancing school administrative effectiveness, with the expectation that it will provide long-term benefits in the more efficient management of educational processes..